Management Model of Cash Waqf for University - Hayati, Isra; Sihotang, Mutiah Khaira; Hamdani, Lukman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
Currently, many campuses have implemented operational fund management through waqf, including the Al-Azhar Egypt campus, Unida Gontor, UII Yogyakarta, and Darunnajah waqf. However, on the other hand, there are still many aspects of management as well as data and management that have not been digitized and published in general. so that this becomes a problem of waqf accountability itself. The purpose of this study is to clearly know the pattern of cash waqf management at the Unida Gontor and MUI campuses and be able to implement this model on all campuses. The methodology of this research is descriptive qualitative with an ANP analysis tool. The results show there are 3 problems in this cash waqf model. Among other things, the HR factor with a rather agreement value of 2%, universities with a rather agreement value of 12% and the operational value of rather agreement at 1%, and the strategy, namely the synergy between BWI and universities, using local wisdom and being used as waqf as a lifestyle with the rather agreement value by 16%.